Penerapan Metode Token Ekonomi dalam Meningkatkan Kedisiplinan Anak Usia 5-6 Tahun di TK ABA Gondanglegi Sutojayan - Assyifa, Nadila; Rocmah, Luluk Iffatur (Universitas Nusantara PGRI Kediri, 2024)
Early childhood education is an effort to provide a place for children from birth to six years, through developmental stimulation so that they are balanced between physical and spiritual. This is to have thorough preparation to pursue further education. Discipline is an attitude or behavior that is embedded in a person's personality in obeying applicable regulations by paying attention to norms, behaving in accordance with existing rules and regulations. Token economy is one of the techniques of behavior modification, designed to increase preferred behavior or reduce disliked behavior by using tokens in the form of coins or other forms of tokens. This study aims to determine the increase in discipline in children aged 5-6 years using the token economy method. This study uses Classroom Action Research (CAR). The subjects in the study were taken from children aged 5-6 years totaling 14 children consisting of 7 boys and 7 girls. The research instrument uses observation, interviews and documentation. Data analysis used qualitative and quantitative. Based on the results of the study, there has been a significant increase in each cycle. Pre-cycle by 32%, cycle I 57% and cycle II 80%. The results of the study indicate that the token economy method can improve the discipline of children aged 5-6 years at ABA Gondanglegi Sutojayan Kindergarten.